Correlation of N-Terminal Pro B-Type Natriuretic Peptide Level with Severity of Coronary Artery Disease in Patients with Non-ST Elevation Acute Coronary Syndrome with Preserved Ejection Fraction - Hassan, Md. Rashidul; Malik, Fazila-Tun-Nesa; Kalimuddin, Md.; Rahman, Faria; Ali, Syed Mahmud; Mostafa-Al-Rasel, Md.; Alam, Md. Shafi-Ul-; Latif, Sayem Bin; Hasan, Md. Mahbub; Khan, Md. Faisal Bin Selim (Cardiology and Cardiovascular Medicine, 2025)
Background: N-terminal pro-B-type natriuretic peptide (NT-pro BNP) has been established as an important biomarker for diagnosis and prognosis of cardiovascular diseases and serum level of NT-pro BNP also elevates in non-ST elevation acute coronary syndrome (NSTE-ACS) with preserved ejection fraction (LVEF ≥50%). The aim of this study was to correlate NT-pro BNP level with angiographic severity of coronary artery disease in patients with NSTE-ACS having preserved ejection fraction (LVEF ≥50%). Methods: This cross-sectional study was conducted in the Department of Cardiology, National Heart Foundation Hospital & Research institute, Mirpur, Dhaka, over a period of one year from 01/08/22 to 31/07/23. Total 156 patients of NSTE-ACS who underwent coronary angiography (CAG) selected purposively were included after considering inclusion and exclusion criteria. Baseline characteristics, biochemical variables including NT-pro BNP, left ventricular ejection fraction (LVEF) and coronary artery disease (CAD) severity by Gensini score were assessed and evaluated. After that study populations were categorized into 3 groups according to Gensini score (GS). In Group A (Low GS, ≤24), 30 (19.2%) patients; Group B (Intermediate GS, 25-53), 46 (29.5%) patients and Group C (High GS, ≥54), 80 (51.3%) patients were assessed. Results: The mean NT-pro BNP levels were 93.07±98.992, 240.04±460.339 & 638.34±645.364 pg/ml in Group A (≤24), Group B (25-53) and Group C (≥54) respectively. The association between NT-pro BNP level with Gensini score was significant (p <0.05). There was positive correlation (r=0.680) observed between NT-pro BNP and Gensini score, which was statistically significant (p <0.05). Multiple logistic regression analysis of predictors of intermediate to high Gensini score (≥25) was evaluated and only NT-pro BNP level was found significant (OR=12.629, 95% CI: 3.52- 45.303, p < 0.0001). Conclusion: NT-pro BNP is significantly associated with the presence and severity of CAD using Gensini score in patients with NSTE-ACS having left ventricular preserved ejection fraction (LVEF ≥50%).